THE EFFECT OF BRAND EQUITY ON REPURCHASE: CONCEPTUAL RESEARCH - Osell Anindya Ayu Aldiona; I Made Sukresna (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to examine brand awareness, perceived quality, brand association, brand loyalty and repurchase interest. This research is a quantitative study with data sources used in this study are primary data and secondary data. The sampling applied in this study uses a plan using a method called the Non Probability Sampling technique. The population planned in this study are Starbucks Coffee visitors so that the sample is taken from buyers who make purchases at Starbuck Coffee outlets. Keywords: Brand Awareness; Perceptions of Quality; Brand Associations; Brand Loyalty; Brand Awareness; Repurchase Interests